PENANGANAN STATUS KEPENDUDUKAN ETNIS ROHINGYA (STUDI KASUS KOTA MAKASSAR) - Asmar, Abd. Rais (Borneo Law Review Journal, 2019)
AbstractThe handling of Rohingya ethnic refugees who entered the city of Makassar due to persecution in their home countries, Myanmar is very necessary because of the vulnerability experienced by Rohingya ethnic refugees, especially this is an international community agreement through the 1951 Convention on Refugees. This vulnerability can occur in children, women, and vulnerability to refugee status. Determination of refugee status is a full right of UNHCR because Indonesia has not ratified the 1951 Convention so that there is no government involvement in this matter both in terms of regulation and action. The fact is that Makassar City is one of the destinations for Rohingya ethnic refugees who want to improve their destiny. The government has issued Presidential Regulation No. 125 of 2016 concerning handling refugees but not yet adequate. As a result, they do not get residence status so they can enjoy educational, health, legal assistance and other needs because of administrative document problems. Therefore, national regulations are needed for them and the role of non-governmental institutions so that ethnic Rohingya refugees can enjoy the facilities available in Makassar City.Keywords: Rohingya Refugees, Population Status???????????????? ?Abstrak??????????????? Penanganan pengungsi etnis rohingya yang masuk ke Kota Makassar akibat persekusi di negara asalnya yaitu Myanmar sangat diperlukan karena kerentanan yang dialami oleh para pengungsi etnis rohingya apalagi ini merupakan kesepakatan masyarakat internasional melalui Konvensi 1951 tentang Pengungsi. Kerentanan tersebut dapat terjadi pada anak-anak, perempuan, maupun kerentanan status pengungsi. Penetapan status pengungsi menjadi hak penuh dari UNHCR karena Indonesia belum meratifikasi Konvensi 1951 sehingga tidak ada keterlibatan pemerintah dalam hal ini baik dalam hal regulasi maupun aksi. Faktanya Kota Makassar menjadi salah satu tujuan pengungsi etnis rohingya yang ingin memperbaiki nasib. Pemerintah telah mengeluarkan Perpres No. 125 Tahun 2016 tentang penanganan pengungsi tetapi belum memadai. Akibatnya mereka tidak mendapatkan status kependudukan sehingga dapat menikmati fasilitas pendidikan, kesehatan, bantuan hukum dan kebutuhan lainnya karena terbentur masalah dokumen adminstrasi. Oleh karena itu, dibutuhkan regulasi nasional yang memadai bagi mereka dan peran lembaga-lembaga non pemerintah agar pengungsi etnis rohingya dapat menikmati fasilitas yang ada di Kota Makassar.Kata Kunci: Pengungsi etnis rohingya, Status kependudukan